1999
DOI: 10.1248/bpb.22.498
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Pharmacokinetics of RS-8359, A Selective and Reversible Inhibitor of A-Type Monoamine Oxidase, in Rats, Mice, Dogs, and Monkeys.

Abstract: RS-8359, (+/-)-4-(4-cyanoanilino)-5,6-dihydro-7-hydroxy-7H-cyclopenta[d]-py rimidine, inhibits, selectively and reversely, A-type monoamine oxidase (MAO-A). In order to clarify the stereoselective metabolism of this drug, plasma concentrations of the [R] and [S]-enantiomers of RS-8359 were determined by chiral column HPLC after oral administration of each enantiomer to rats, mice, dogs, and monkeys. After administration of the [R]-enantiomer, high levels were retained in all animal species studied. On the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Previous metabolic studies on RS-8359 revealed that one of the major metabolic pathways is the stereoselective 2-oxidation of the (S)-enantiomer of RS-8359 catalysed by aldehyde oxidase [7,9]. Marked species differences were shown in enzyme activity, it being much higher in monkeys and humans and deficient in dogs [8,9]. The findings agree with the well-known species differences in aldehyde oxidase [13][14][15][18][19][20].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous metabolic studies on RS-8359 revealed that one of the major metabolic pathways is the stereoselective 2-oxidation of the (S)-enantiomer of RS-8359 catalysed by aldehyde oxidase [7,9]. Marked species differences were shown in enzyme activity, it being much higher in monkeys and humans and deficient in dogs [8,9]. The findings agree with the well-known species differences in aldehyde oxidase [13][14][15][18][19][20].…”
Section: Discussionsupporting
confidence: 84%
“…Roughly, the degree of aldehyde oxidase activity is high in monkeys and humans, moderate in rats and mice and deficient in dogs. The large species differences shown in the in vivo [8,9] and in vitro [11] metabolism of RS-8359 were highly consistent with those already reported.…”
Section: Rs-8359 [ðAeþ-4-(4-cyanoanilino)-56-dihydro-7-hydroxy-7h-csupporting
confidence: 91%
“…Being fundamentally different from XOR, AOX1-catalyzed drug metabolism results in marked species differences, which have been well documented for methotrexate (Jordan et al, 1999;Kitamura et al, 1999), famciclovir (Rashidi et al, 1997), cinchona alkaloids (Beedham et al, 1992;Itoh et al, 2006), zonisamide (Kitamura et al, 2001), and a monoamine oxidase A inhibitor RS-8359 (Takasaki et al, 1999(Takasaki et al, , 2005Itoh et al, 2005Itoh et al, , 2006. As a rule, AOX1 activity is high in monkeys and humans, moderate to low in rabbits, rats, and mice, and deficient in dogs.…”
mentioning
confidence: 97%
“…Previous metabolic studies on RS-8359 revealed that the (S)-enantiomer of the compound disappeared extremely rapidly from the plasma in every animal species as compared to the (R)-enantiomer after oral administration to rats, mice, dogs, monkeys, and humans. 7,8 The AUC(R)/AUC(S) ratios were 2.6 in rats, 3.8 in mice, 31 in dogs, and 238 in monkeys.7 The (S)-enantiomer was not substantially detected in human plasma. The in vivo and partially in vitro metabolism studies in rats demonstrated that the enantioselective pharmacokinetics might be caused by the enantioselectivity of metabolism, but not intestinal absorption, tissue distribution, and urinary or biliary excretion.…”
mentioning
confidence: 97%